2017
DOI: 10.1007/s13365-017-0524-1
|View full text |Cite|
|
Sign up to set email alerts
|

White matter measures are near normal in controlled HIV infection except in those with cognitive impairment and longer HIV duration

Abstract: The objective of the current study was to quantify the degree of white matter (WM) abnormalities in chronic and virally suppressed HIV-infected (HIV+) persons while carefully taking into account demographic and disease factors. Diffusion tensor imaging (DTI) was conducted in 40 HIV− and 82 HIV+ men with comparable demographics and life style factors. The HIV+ sample was clinically stable with successful viral control. Diffusion was measured across 32 non-colinear directions with a b-value of 1000 s/mm 2 ; frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Lastly, this study analyzed global measures of brain structure acquired on 1.5 Tesla systems. Future studies should utilize scanners with greater field strength (e.g., 3 Tesla) as well as examine specific brain structures and other imaging modalities such as functional MRI and diffusion tensor imaging that have been shown to be sensitive to cognitive functioning in HIV (Ances et al, 2009;Cysique et al, 2017;du Plessis et al, 2017;Masters & Ances, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, this study analyzed global measures of brain structure acquired on 1.5 Tesla systems. Future studies should utilize scanners with greater field strength (e.g., 3 Tesla) as well as examine specific brain structures and other imaging modalities such as functional MRI and diffusion tensor imaging that have been shown to be sensitive to cognitive functioning in HIV (Ances et al, 2009;Cysique et al, 2017;du Plessis et al, 2017;Masters & Ances, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Zhuang Y et al investigated WM changes in ANI patients diagnosed according to the Frascati criteria [ 3 ] and found no significant WM microstructural differences between HIV-infected and healthy controls [ 18 ]. Cysique LA et al reported that the location of WM injury in ANI cases was the anterior limb of the internal capsule [ 19 ]. The above findings still exhibit differences.…”
Section: Introductionmentioning
confidence: 99%
“…While our focus in this analysis is radiation‐induced white matter and cognition, the effect of damage and cognition has been shown in non‐radiation related injury. Among persons living with HIV, the white matter measures deviate from normal and are associated with impaired cognition (Cysique et al., 2017). In children with multiple sclerosis where the myelin is progressively attacked by the immune system, the white matter FA and cognitive processing speed are correlated (Bethune et al., 2011).…”
Section: Discussionmentioning
confidence: 99%